2010
DOI: 10.1002/mats.201000031
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline/Crystalline Phase Transitions in Polymer Systems Consisting of Finite‐Size Crystals in Each Crystalline Phase: Generalized Gibbs‐Thomson Equation

Abstract: For polymer systems of two crystalline phases of one polymer component, each phase being consisted of polymer crystals of a finite size, we derive the crystalline‐crystalline phase transition relationship, i.e., generalized Gibbs‐Thomson equation. Its application combined with the crystalline‐liquid transition relationship (usual Gibbs‐Thomson equation) to the phase behavior of PT phase diagram of polyethylene (PE) is investigated, where the orthorhombic‐hexagonal phase transition of PE crystal under high pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have shown that the thermal properties of materials are affected by the size and distributions of the melting crystals. , Using Gibbs free energy for constructing the crystalline state from melt, several research groups derived the phase transition relationship for lamellar crystals in polymer systems (generalized Gibbs–Thomson equation) when crystallization and melting occurs on the lateral crystal phase by removal of a complete sequence: T i = T i 0 true( 1 2 normalσ e i l i normalΔ H u i true) where T i is the melting temperature of a finite sized polymer crystal of thickness l i , T 0 i is the equilibrium melting temperature (melting point) of an infinitely large crystal ( l i → ∞), and σ is the surface energy at the lamellar interface, and, Δ H ui is melting enthalpy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the thermal properties of materials are affected by the size and distributions of the melting crystals. , Using Gibbs free energy for constructing the crystalline state from melt, several research groups derived the phase transition relationship for lamellar crystals in polymer systems (generalized Gibbs–Thomson equation) when crystallization and melting occurs on the lateral crystal phase by removal of a complete sequence: T i = T i 0 true( 1 2 normalσ e i l i normalΔ H u i true) where T i is the melting temperature of a finite sized polymer crystal of thickness l i , T 0 i is the equilibrium melting temperature (melting point) of an infinitely large crystal ( l i → ∞), and σ is the surface energy at the lamellar interface, and, Δ H ui is melting enthalpy.…”
Section: Discussionmentioning
confidence: 99%